Vertical structures and drivers of marine heatwaves and cold-spells in the Kuroshio Extension region - Qiang Xu; Kai Liu; Haiyan Wang; Xingrong Chen (Environmental Research Letters, 2024)
Marine heatwaves (MHWs) and marine cold-spells (MCSs) are prolonged oceanic extreme temperature events that can severely impact large-scale ecosystems, fisheries, and human activities with consequent socioeconomic impacts. Although some studies have contributed valuable insights into the vertical structure and related mechanisms of MHWs, equivalent research on MCSs remains unclear. Thus, comprehensive and systematic analysis of the vertical structures and related mechanisms of MHWs and MCSs remains area of an active research. In this study, we classified MHWs/MCSs into two types in the Kuroshio Extension region: extended MHWs/MCSs that can extend through more than 70% of the water column and shallow MHWs/MCSs that are restricted from the surface layer to less than 70% of the water column. Analysis revealed that shallow events are characterized by stronger intensity and shorter duration compared with extended events. All shallow events are driven by surface heat flux anomalies, with shortwave radiation (latent heat flux) mostly inducing those in MHWs (MCSs). However, extended MHWs/MCSs are primarily driven by ocean anticyclonic/cyclonic eddies. These findings provide deeper understanding of the statistical characteristics, vertical structures, and physical drivers of MHWs and MCSs.